Pheochromocytoma Sudden Death as a Result of Cerebral Hemorrhage - Kır, Muhammed Ziya; Pakiş, Işıl; Özaslan, Abdi; Özbay, Mehmet (The Bulletin of Legal Medicine, 2005)
Pheochromocytoma is an endocrine tumor characterized by severe hypertension associated with cerebral, cardiac, and renal complications, hypotension or even shock and sudden death. Most pheochromocytoma cases remain obscene clinically, fatal outcome is mostly related with such misdiagnosis. A 17-year-old girl with a history of chronic headache who had not been evaluated clinically died unexpectedly. The autopsy performed in the mortuary section of the council of forensic medicine revealed a pheochromocytoma and intraventricular cerebral bleeding. This case accentuates that pheochromocytomas, if remaining undiagnosed, may prove fatal. Key words: pheochromocytoma; death; autopsy